The epidemiology of adults with severe sepsis and septic shock in Scottish emergency departments. Issue 5 (29th June 2012) - Gray, Alasdair; Ward, Kirsty; Lees, Fiona; Dewar, Colin; Dickie, Sarah; McGuffie, Crawford; ,
Abstract : Background: The Surviving Sepsis Campaign (SSC) promotes a bundle approach to the care of septic patients to improve outcome. Some have questioned the capability of delivering the bundle in emergency departments (EDs). The authors report the epidemiology and 6 h bundle compliance of patients with severe sepsis/septic shock presenting to Scottish EDs. Methods: Analysis of the previously reported Scottish Trauma Audit Group sepsis database was performed including 20 mainland Scottish EDs. A total of 308 910 attendances were screened (between 2 March and 31 May 2009), and 5285 of 27 046 patients were identified after case note review and included on the database. This analysis includes patients who had severe sepsis/septic shock before leaving the ED. Epidemiological, severity of illness criteria, and ED management data were analysed. Results: 626 patients (median age 73; M/F ratio 1:1; 637 presentations) met entrance criteria. The median number of cases per site was 16 (range 3–103). 561 (88.1%) patients arrived by ambulance. The most common source of infection was the respiratory tract (n=411, 64.5%) The most common physiological derangements were heart rate (n=523, 82.1%), respiratory rate (n=452, 71%) and white cell count (n=432, 67.8%). The median hospital stay was 9 days (IQR 4–17 days). 201 (31.6%) patients were admitted to critical care within 2 days, 130 (20.4%) directly from the ED. 180 patients (28.3%) died. There was poor compliance with all aspect of the SSC resuscitation bundle. Conclusions: Sepsis presentations are of variable frequency but have typical epidemiology and clinical outcomes. SSC bundle resuscitation uptake is poor in Scottish EDs.